Electrocardiographic parameters in clinically healthy Balouchi sheep - Tahmineh Tajik; Alireza Taghavi razavizade; Mohammad Reza Aslani; Javad Tajik (The Iranian Journal of Veterinary Science and Technology, 2015)
Electrocardiographic (ECG) parameters and cardiac rhythms have been evaluated and published in different breeds of beef and dairy cattle but there is limited information regarding these parameters in healthy sheep. This study is aimed to investigate the ECG parameters in Balouchi sheep. The ECG parameters including the amplitudes of P, Q, R, S and T waves, duration of P, QRS and T waves and P-R, Q-T and R-R intervals were evaluated in 44 male and female clinically healthy Balouchi sheep in standard and augmented limb leads (I, II, III, AVR, AVL, and AVF) and base-apex lead. The mean heart rate was 89.6 beats/minute which had a significant correlation with age (r=-0.269, p=0.014). Different configurations of P-wave, QRS complex and T wave were observed in different ECG leads. It was found that age and gender affects some ECG parameters. In some leads, rams had significantly higher amplitudes of P, Q, R, S and T waves and longer duration of PRR interval than ewes. Also in some leads, the amplitudes of P, R and S waves were significantly higher and the duration of QRS complex was shorter in sheep less than one year old than sheep with age three years or older. The most common cardiac dysrhythmia observed on the ECG traces was Sinus arrhythmia. Sheep with this dysrhythmia had a significantly lower heart rate (p